Strategies to Investigate Ubiquitination in Huntington's Disease - Sap, Karen A.; Reits, Eric A. (Frontiers in Chemistry, 2020)
Many neurodegenerative disorders including Huntington’s Disease are hallmarked by intracellular protein aggregates that are decorated by ubiquitin and different ubiquitin ligases and deubiquitinating enzymes. The protein aggregates observed in Huntington’s Disease are caused by a polyglutamine expansion in the N-terminus of the huntingtin protein (Htt). Improving the degradation of mutant Htt via the Ubiquitin Proteasome System prior to aggregation would be a therapeutic strategy to delay or prevent the onset of Huntington’s Disease for which there is currently no cure. Here we examine the current approaches used to study the ubiquitination of both soluble Htt as well as insolubilized Htt present in aggregates, and we describe what is known about involved (de)ubiquitinating enzymes. Furthermore, we discuss novel methodologies to study the dynamics of Htt ubiquitination in living cells using fluorescent ubiquitin probes, to identify and quantify Htt ubiquitination by mass spectrometry-based approaches, and various approaches to identify involved ubiquitinating enzymes.